Excessive boron fertilization-induced toxicity is related to boron transport in field-grown pomelo trees - Luo, Ziwei; Zhang, Lijun; Hu, Wenlang; Wang, Yuwen; Tao, Jingxia; Jia, Yamin; Miao, Ruizhen; Chen, Li-Song; Guo, Jiuxin (Frontiers in Plant Science, 2024)
Boron (B) is an essential micronutrient for plant growth and development; however, the process of B toxicity in citrus production is still poorly understood. We proposed a hypothesis that B toxicity in citrus trees is related to the characteristics of B transport from soil to leaf or fruit. For this, a field experiment was conducted for two treatments: control (B free or without B) and B fertilizer treatment (100 g Na2B4O7·10H2O plant-1), to investigate the effects on plant growth, nutrient uptake, fruit yield and quality, and B transport in 10-year-old pomelo trees (Citrus grandis (L.) Osbeck cv. Guanximiyou). Our results showed that excess B fertilization directly led to B toxicity in pomelo trees by dramatically increasing soil total B and water-soluble B contents. B toxicity induced interveinal chlorosis in leaves and decreased leaf biomass and function, resulting in a decreased 45.3% fruit yield by reducing 30.6% fruit load and 21.4% single fruit weight. Also, B toxicity induced changes in mineral elements between leaf positions and fruit parts, in which the concentrations of B, potassium, and magnesium were increased while nitrogen and iron were decreased. Under B toxicity conditions, fruit quality parameters of total soluble solids (TSS), TSS/titratable acidity (TA), total soluble sugar, sucrose, pH, vitamin C, and total phenol contents were decreased, which regulated by the lower carbohydrate production in new leaves and the lower transport capacity in old leaves. Moreover, B toxicity significantly increased the transfer factor and bio-concentration factor of B in pomelo plants, with higher levels in leaf organs than in fruit organs. Taken together, excess B fertilization-induced B toxicity in pomelo trees, with induced growth inhibition and nutrient disorder, results in reduced fruit yield and quality, which are related to B transport from soil to organs. The findings of this study highlight the understanding of B toxicity in citrus plants and strengthening B management in pomelo production for high yield and high quality.